Descriptive analyses on the new biotype of weedy rices in Selangor North-West project, Malaysia / Muhamad Shakirin bin Mispan - Mispan, Muhamad Shakirin (2008)

(untitled)
Weedy rice (Oryza sativa . L) is a big threat in rice industry all over the world an also in Malaysia. The infestation of weedy rice caused a big loss to production and yield to the rice farmers. Study in Selangor North West Project for three consecutive seasons in 2006 to 2008 has found a new variety or biotype of weedy rice which has infested rice granaries here. In general, weedy rice is taller than any cultivated rice and it is very to be identified. However, this new biotype of weedy rice (NBWR) stands as tall as any cultivated rice namely MR220 and MR219. As such these NBWR accessions stand among equals morphologically vis-à-vis the commercial varieties of rice i.e. MR220, MR219 and MR232. Spatial distribution analysis through quantitative index, Variance to mean ratio and Lloyd patchiness index, has found that most NBWR accessions were distributed in clump or cluster and only some of them were distributed randomly. From this Fig., Acc 8 has the highest population and was most dominant accession while Sawah Sempadan was the worst farm block infested by NBWR compared to other farms. Descriptive analysis has observed that NBWR accessions have close morphological traits and really mimic the cultivated rice viz. MR220, MR219 and MR84. Multivariate analysis has resulted some characters and traits which can be used to differentiate between MR220 and NBWR accessions. Results show that qualitative characters such as panicle type and pericarp colour can be most important characters to differentiate these plants. Seed germination and growth pattern test have found NBWR was easy to germinate in control environment.However, a few factors seem to disturb the germination. NBWR seeds cannot be germinated in high temperature over 40oC and low temperature below 20oC; soil depth below 5cm and water level below 7cm. On the other hand light does not affect the germination. Competition between NBWR and cultivated rice var. MR220 has found the relationship between these two plants. Results found that MR220 did not affected by the existence of NBWR but not to NBWR. NBWR was affected quite badly in any density regime. This has concluded that the existence of NBWR will not give any problem in rice field. Path analysis has found the relationship between rice density and weed density in affecting the yield components. High density in weed and rice can affect the yield components for both MR220 and NBWR. However, the difference in yield components will not give any obvious impact to the fecundity of rice and weed.